2020
DOI: 10.1186/s12915-020-00827-y
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering anthrax toxin protective antigen for improved receptor-specific protein delivery

Abstract: Background: To increase the size of the druggable proteome, it would be highly desirable to devise efficient methods to translocate designed binding proteins to the cytosol, as they could specifically target flat and hydrophobic protein-protein interfaces. If this could be done in a manner dependent on a cell surface receptor, two layers of specificity would be obtained: one for the cell type and the other for the cytosolic target. Bacterial protein toxins have naturally evolved such systems. Anthrax toxin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Cloning of most constructs used in this study has been described before [ 6 , 9 ]. DARPin cargoes were cloned into the SpeI/AgeI-restricted pQIq-LF N -cargo-avi-HA backbone for protein delivery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning of most constructs used in this study has been described before [ 6 , 9 ]. DARPin cargoes were cloned into the SpeI/AgeI-restricted pQIq-LF N -cargo-avi-HA backbone for protein delivery.…”
Section: Methodsmentioning
confidence: 99%
“…The modular structure of anthrax toxin enabled us and others to generate engineered PA variants with altered cell specificity and the capability to translocate alternative LF cargo molecules [ 4 , 5 , 6 , 7 , 8 , 9 ]. Our group and others [ 6 , 10 , 11 , 12 , 13 ] showed that cytosolic translocation by pore-forming toxins depends on the ability of the molecule to fit through this channel.…”
Section: Introductionmentioning
confidence: 99%
“…As a starting point, it is useful to consider that approaches that report cytosolic protein delivery in 2D systems in vitro often report values of cytosolic concentrations for the delivered protein that are comparatively high (mid- or high-nanomolar range) [ 18 , 24 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], which is well over the average level of molecules of a specific protein in a cell, which is around 2000–8000 molecules/cell (~2–10 nM) [ 27 ]. Hence, addressing cytosolic targets in vitro is already possible for some applications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Becker et al used designed ankyrin repeat proteins (DARPins) fused to a PA-CMG2-based construct to specifically target transmembrane glycoprotein epithelial cell adhesion molecule (EpCAM) at the surface of cells. These engineered constructs were shown to target EpCAM-expressing cells with a high specificity and to deliver LF N -based constructs to the cytosol [ 58 ]. Overall, these engineered proteins show that both the A and B subunits of anthrax toxin have strong potential as a protein delivery system, and they open many new routes for investigating the development of therapeutics.…”
Section: Anthrax Toxinmentioning
confidence: 99%
“…Targeting to non-native receptors using Affibodies, DARPins or receptors ligand for the cytosolic delivery of non-native cargos [ 55 , 56 , 57 , 58 ]…”
Section: Figurementioning
confidence: 99%